(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The thirst for production from harmful occupational factors is in many cases the etiology of COPD. The article examined the issues of timely diagnosis, relevance of the issues of treatment and Prevention and the importance of linking the disease to a professionally harmful factor. Workers who work under the influence of a harmful professional factor are more notable due to the increasing problem of labor intensity, quality, environmental pollution, occupational diseases. Our controlled patients have been treated with a diagnosis of COPD. We aim to approach the disease from the point of view of occupational diseases and study the issues of importance in treating the disease, preventing its complications. Patients were treated in the city hospital. When we studied their disease histories, we came to the idea that a deeper study of the etiology of the disease was necessary. Because COPD etiology WHO statistics show that 80% of oosok-related deaths occur in low-and moderate-income countries per capita. Thus, the occurrence of this disease is partly directly related to the lifestyle and conditions of a person, the environmental well-being around him and the possibility of early diagnosis of the disease. Diseases of the pulmonary-bronchial system in most cases, it may be enough to relieve the patient’s condition and restore strength, improve his quality of life, eliminate the source of the disease to the goal.